2016
DOI: 10.5154/r.rchsza.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta del olivo (Olea europaea L.) ‘Manzanillo’ a la aplicación de biorreguladores y urea foliar y su interacción con altas temperaturas

Abstract: Para mejorar el amarre y rendimiento de frutos en árboles de olivo se evaluaron biorreguladores y urea vía foliar durante tres ciclos y su interacción con altas temperaturas. Además, se llevó a cabo un análisis empírico de la inf luencia de temperaturas altas sobre el amarre de frutos. No se encontraron diferencias estadísticas en rendimiento (un ciclo) entre los tratamientos evaluados. Sobresaliendo Cytokin, Maxigrow y el Testigo con rendimientos superiores a 6.2 t.ha-1, así como mayor número de inf lorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Picual yield, leaf mineral content and fruit properties which comes in contrast with obtained data from cv. Manzanillo olive trees in Mexico where urea application did not be proven as valuable to alleviate of low fruit set in high temperatures (Abd El Migeed et al 2017;Navarro-Ainza et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Picual yield, leaf mineral content and fruit properties which comes in contrast with obtained data from cv. Manzanillo olive trees in Mexico where urea application did not be proven as valuable to alleviate of low fruit set in high temperatures (Abd El Migeed et al 2017;Navarro-Ainza et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Navarro-Ainza and López-Carvajal (2013) confirmed that a temperature above 30°C restricts fruit-setting, and Navarro-Ainza et al (2016) determined that the ideal temperature is 25°C; in this sense, the temperature in the Alto Ricaurte is on average 27.6°C, consequently, it stimulates fruitsetting, but the olive varieties in this region are not accurately known.…”
Section: Number Of Flowers and Inflorescencesmentioning
confidence: 99%